Changes in the English Jury in the 19th and 20th Centuries - Antal, Tamás (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The present paper deals with the short history of the English jury in the modern age. The main goal of the author is completing a historical investigation and finding the most important features concerning to the legal institutions of the Anglo-Saxon type of lay jurisdiction in England (Great-Britain) and Ireland. The historical perspective gives a chance to examine the institutions of the jury as a court of citizens integrated into the jurisdiction of the state for a brief period of time. The author takes the view in several periods from the early 19th century up to the end of the 20th century. It is not the procedure but the organisational rules which are under discussion here with special attention to the conditions determined the role of the jury as a part of county courts and sessions as well as the central tribunals in London. The literature was collected in the British Library during research intervals to have the opportunity to work with special sources not cited by Central-European scholars yet.